Penerapan Kelas Virtual Sevima Edlink untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika dengan Pendekatan Saintifik - Khusnul Khotimah; Lailatul Maghfiroh (JoEMS (Journal of Education and Management Studies), 2022)
This study aims to determine whether there is an increase in students' mathematical problem solving skills using a scientific approach to the virtual class Sevima Delink. This research was carried out in class XI MA Superior Wahab Chasulloh Jombang. The samples of this study were students of class XI IIA-1 as a control class by getting learning without using a virtual class Sevima edlink and students of class XI MIPA-1 as an experimental class with learning using a virtual class Sevima edlink. The research method used is quantitative research with the type of experimental research method quasi-experimental design. Data was collected by giving tests in the form of pretest and posttest. The results of the study show that learning with the virtual class Sevima is more edlinked with a scientific approach is more effective in improving mathematical problem solving skills compared to conventional learning.